A 4H–SiC double trench MOSFET with split gate and integrated MPS diode. (October 2022) - Peng, Disen; Feng, Quanyuan
Abstract: A 4H–SiC double trench MOSFET with split gate and integrated MPS(Merged PiN Schottky) diode (MPS-SGMOS) is proposed, and simulated by Sentaurus TCAD tools. The introduction of the P+ shielding region ensures the reliability of the gate oxide of the device, reduces the electric lines of force gathered at the bottom of the gate oxide, and improves the withstand voltage of the device; the introduction of the Schottky diode enables the device to obtain better reverse recovery performance; adding a source electrode between the split gate reduces the Cgd greatly and the switching losses of the device, so that the device is more suitable for high frequency applications. As a result, comparing to conventional double-trench MOSFET (Con-DTMOS), MPS-SGMOS owns comparable on-state characteristics, while its breakdown voltage is increased by 10.5%. The FOM(figure of merit) of R on, sp × Q gd, sp is decreased by 78.2% compared to the traditional device, moreover the peak reverse recovery charge is decreased by 32.7%.